Static test compaction for mixed broadside and skewed‐load transition fault test sets. Issue 1 (1st January 2013) - Pomeranz, Irith
Abstract : Test sets that consist of both broadside and skewed‐load tests provide improved delay fault coverage for standard‐scan circuits. This study describes a static test compaction procedure for such test sets. The unique feature of the procedure is that it can modify the type of a test (from broadside to skewed‐load or from skewed‐load to broadside) if this contributes to test compaction. Given a test set W, the basic static test compaction procedure described in this study considers for inclusion in the compacted test set both a broadside and a skewed‐load test based on every test w ∈ W . It selects the test type that detects the higher number of faults. An improved procedure considers a broadside and a skewed‐load test based on a test w ∈ W only if w detects a minimum number of faults (without changing its type). Experimental results demonstrate that the static test compaction procedure is typically able to reduce the sizes of mixed test sets further than a procedure that does not modify test types. The procedure modifies the types of significant numbers of tests before including them in the compacted test set.